Environmental crime predictors and the spatial distribution of crime. The case of stare Baluty in Lodz, Poland - Mordwa, Stanisław; Laskowska, Patrycja (Space – Society – Economy, 2020)
The article refers to various studies on the creation of safe spaces as well as works on the influence of land-use on the distribution of crime in urban space. The goal of the study is to identify places and facilities which constitute a potential threat to safety and impact the spatial distribution of crime. An analysis of relationships between various types of crime predictors and the spatial distribution of crimes at the address-level has also been made. The most important conclusion drawn from the study is that the distribution of crime predictors strongly impacts the presence of crime in their direct vicinity and this influence on crime gradually lessens as the distance increases. The influence of such crime predictors as honeypots and public facilities on attracting crime as well as movement predictors and conflicts of land use on repelling crime was determined.